Genetic variation for growth, wood and fibre properties of Pinus patula families grown on six sites in South Africa. - Vermaak, J. A. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2007.